"What hypocrites!": interactions between Japanese international and white domestic students in a U.S. teacher education programme. Issue 2 (15th March 2021) - Amos, Yukari Takimoto
ABSTRACT: This two-year-long qualitative study investigated how white teacher candidates at a U.S. university interacted with two international teacher candidates from Japan. Findings reveal that the participants stopped interacting with their white peers because the interactions did not occur on equal grounds, and they disliked the fact that they were always positioned as lower and subordinate. The participants were resistant to the new power relations in which they were embedded. Ironically, the more the participants withdrew, the more solid the power hierarchy became as it proved their inferiority from the perspective of their white peers. The study ends with strategic suggestions for creating more meaningful interactions between domestic and international students.